Oriental reading of the Quranic text - Alwahad, Noor; Abbas, Muhammad (Al-Adab Journal, 2024)
The orientalists’ reading of the Holy Qur’an is one of the issues that Muhammad Arkoun cared about, and it is part of his project to criticize the orientalist reading in general for the Islamic heritage. The issues dealt with by Orientalism, and then the transfer of the Islamic heritage to the Western reader, by standing on the analysis, explanation and criticism of Arkoun’s propositions, in order to understand some Orientalists of the Holy Qur’an.